Dried distillers grains with solubles ability to effectively replace soybean meal in Boer goat diets - Smith, Maggie J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Literature regarding dried distillers grains with solubles (DDGS) fed to Boer goats is limited. Feed costs account for 65% of total production costs, which makes research assessing ways to increase the effectiveness of livestock feeds with DDGS highly valuable. Compared to soybean meal (SBM), DDGS are a more economic source of protein, cutting feed costs by $1.86 per protein unit. However, limited research restricts goat producers and small ruminant nutritionists from making these economical feed changes. The primary objective of this experiment was to evaluate the efficacy of DDGS as a replacement for SBM in a Boer goat diet. Forty-eight meat goat kids (approximately 70 d of age, initially 28.2 kg) were analyzed in a completely randomized design, and housed within the Kansas State University Sheep and Meat Goat Center. Three kids were randomly assigned per pen, with four pens per treatment. Pens were allotted into one of four experimental diets: 1) 0% DDGS; 2) 33% DDGS; 3) 66% DDGS; and 4) 100% SBM replaced by DDGS. Complete diets were pelleted and fed for 47 days, while goats and feeders were weighed weekly to determine ADG, ADFI, and G:F. At the conclusion of the feeding period, two goats per pen were harvested at a USDA inspected abbatoir, where carcass data was collected. Data was analyzed utilizing the GLIMMIX procedure (SAS 9.4, Cary, NC). Pen served as the experimental unit and results were considered significant when P < 0.05. Dietary treatment significantly impacted (P < 0.0001) overall G:F, but not overall ADG or ADFI (P > 0.10). This finding was due to a linear improvement (P < 0.02) in overall ADG and G:F with increasing amounts of DDGS. Overall, the greatest (P < 0.05) feed efficiency was observed in goats fed 66% or 100% of SBM replaced by DDGS, compared to those fed 0% or 33% of SBM replaced by DDGS. There was no impact (P > 0.10) of DDGS inclusion on any measured carcass variable. In summary, inclusion of DDGS in place of SBM within Boer type goat diets can improve G:F while maintaining impacts within ADG, ADFI and carcass variables.
Keywords: Spring 2018